Road Geometric Redesign used AutoCAD 2D A Case Jalan Majalengka-Rajagaluh - Anugraha, Pebri Tri; Irfan Rifai, Andri (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2024)
Majalengka-Rajagaluh road is a road located in several sub-districts which is a link to the city and also one of the connecting roads to Cirebon City. This design planning starts in Cigasong sub-district and continues to Rajagaluh sub-district with the length of Majalengka-Rajagaluh road is 5.3 kilometers. The geometric design results are visualized in the form of drawings using AutoCAD 2D. The design speed (Vd) was set at 60 km/h with a horizontal curve radius of 358 m, a maximum slope of 4%, and an elevation (e max) of 8%. Based on these design criteria, a spiral curve with a circular curve length (Lc) of 74.996 m was obtained. Furthermore, the results of the vertical alignment calculation of the length (L) of one type of convex curve in PPV were also calculated.